American empire and the relative autonomy of European capitalism. (April 2015) - Panitch, Leo; Gindin, Sam; Aquanno, Scott M
This article examines the relationship between European states and the informal American empire following the Second World War. Building on neo-Marxist theory, it argues that any attempt to understand the political response to the ongoing euro crisis has to consider the deeper determinations of the trajectories of the states of North America and Western Europe through the course of the making of global capitalism since 1945. This involves, in particular, taking seriously the leading responsibility that the American state has had, and still has, for securing the conditions for capital accumulation internationally, even while other capitalist states retain their 'relative autonomy' within the informal American empire.